Emerging threats and vaccination strategies of H9N2 viruses in poultry in Indonesia: A review [version 2; peer review: 2 approved] - Rehman, Saifur; Rantam, Fedik Abdul; Batool, Khadija; Shehzad, Aamir; Effendi, Mustofa Helmi; Witaningrum, Adiana Mutamsari; Bilal, Muhammad; Elziyad Purnama, Muhammad Thohawi (F1000 research, 2022)
Avian influenza virus subtype H9N2 was first documented in Indonesia in 2017. It has become prevalent in chickens in many provinces of Indonesia as a result of reassortment in live bird markets. Low pathogenic avian influenza subtype H9N2 virus-infected poultry provides a new direction for the influenza virus. According to the latest research, the Indonesian H9N2 viruses may have developed through antigenic drift into a new genotype, posing a significant hazard to poultry and public health. The latest proof of interspecies transmission proposes that the next human pandemic variant will be the avian influenza virus subtype H9N2. Manipulation and elimination of H9N2 viruses in Indonesia, constant surveillance of viral mutation, and vaccine updates are required to achieve effectiveness. The current review examines should be investigates/assesses/report on the development and evolution of newly identified H9N2 viruses in Indonesia and their vaccination strategy.